Karakteristik Beton Mutu Tinggi Dengan Komposisi Slag dan Agregat Halus Batu Gamping - Dicaprio Resen Bunga'; Frans Phengkarsa; Desi Sandy (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
In general, fine aggregate and coarse aggregate as the main components of concrete come from nature so that one day it will run out, alternative substitutes are needed. One of the alternative materials is Nickel Slag. Nickel slag is a type of rock dumped from the nickel industry. Limestone is also used as an alternative to fine aggregate. This study aims to determine the strength of concrete and the relationship between the characteristics of the concrete using nickeI sIag and limestone as a substitute for fine aggregate to the quality of the concrete. As for the variations of 0%, 10% and 20% and the percentage of using limestone as a substitute for fine aggregate is 10%. The method of mixing the concrete uses the SNI-03-2834-2000 method with a planned concrete quality of 42Mpa. From this research, it was found that the compressive strength of concrete with variations of 0%, 10% and 20% were respectively 42.360 MPa, 42.347 MPa and 41.781 MPa, the split tensile strength test with variations of 0%, 10% and 20% respectively was equal to 3.94 MPa, 3.064 MPa and 2.293 MPa and the flexural strength testing with variations of 0%, 10% and 20% were respectively 4.242 MPa, 4.068 MPa and 3.179 MPa. The relationship of split tensile strength for the variation of Nickel Slag variations 0%, 10%, and 20% is 9,242%, 7,178%, and 7% of the compressive strength, respectively, the relationship of split tensile strength for the variation of Nickel Slag variations 0%, 10%, and 20% of 0.65, 0.62, and 0.57 of compressive strength, respectively. From the resuIts of the study, it was concIuded that the concrete mixture with nickel and limestone slag substitution resulted in a decrease in strength as the percentage of nickel slag substitution increased.